Acute toxity and sublethal eff ects of pymetrozine on the whitefl y parasitoid Encarsia formosa Gahan - Drobnjaković, Tanja; Marčić, Dejan (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2020)
Sublethal eff ects of a pymetrozine-based product (commercial product Chess 50 WP) on life history traits and population growth of one commercialized strain (“Dutch” strain) and two local populations (Bujanovac and Negotin) of the whitefl y parasitoid Encarsia formosa Gahan (Hymenoptera: Aphelinidae) were evaluated in laboratory bioassays. All trials were carried out at 27±1°C temperature and under 60±10 % relative humidity and 16/8 h daylight/darkness photoperiod in four replications. Longevity of wasps exposed for 48 h to residues of the pymetrozine insecticide (LC50, 280 mg a.i./l) was shorter (by 2.7-3 days) than that of control wasps. Total parasitism of Negotin wasps was significantly reduced (by 8.2 %), as well as total parasitism and adult emergence of the Dutch strain (by 7.3 and 8.2 %, respectively), compared to control wasps. The instantaneous rate of increase (ri) of surviving adult wasps was also signifi cantly reduced (by 6.6, 6.3 and 7.6 % in populations Negotin, Bujanovac and Dutch strain, respectively). Direct treatment of wasps at their pupal stage (LC50, 300 mg a.i./l) reduced total parasitism of Negotin wasps (by 8 %), and reduced ri levels, but the reduction was signifi cant only for the Bujanovac (by 6.7 %) and Negotin (by 4.6 %) populations. Juvenile development of the parasitoid in treated pupae was signifi cantly extended (by 0.3-1.1 days), compared to control wasps. The implications of these results on integrated control of the greenhouse whitefl y are discussed.
Keywords: Encarsia formosa; pymetrozine; sublethal effects; life history traits; population growth